Attitudes of prospective spouses towards moral principles regulating procreative behaviors - Dudziak, Urszula (Kwartalnik Naukowy Fides et Ratio, 2022)
The ability of transmission life is a precious gift for both spouses and society as a whole. This gift is protected by moral principles that show the need to reject anything that goes against responsible parenting. However, it can be noticed that when some people appreciate the possibilities of reproduction and living in harmony with their own sexuality and fertility, others struggle with it. They do not recognize fertile and infertile days of the cycle, but eliminate fertility through contraceptives and even allow abortion. In the case of problems with conception, some decide to undergo in vitro fertilization, regardless of the instrumentalisation and medicalization of procreation, the death of some embryos as part of the procedures undertaken, or the possible negative health effects. The article consisting of three parts regres 1.x1qto passages from Holy Scripture and numerous documents of the Catholic Church on procreation and moral principles in the field of transmitting human life. In this way, it answers the question ’how should it be?’. The answer to the question ’how is it?’ becomes possible thanks to the research, especially prepared for this purpose, questionnaire: Attitudes towards marital and family morality. The respondents were people preparing for marriage as part of courses organized by parishes in villages near Lublin. It would seem that the inhabitants of smaller towns pay more attention to the opinions of others than the anonymous inhabitants of cities, and it is conducive to maintaining moral norms and living in accordance with them. However, the polls of a large part of the respondents indicate serious discrepancies between the indications of the Catholic Church and the attitudes expressed. Although the vast majority define themselves as ’believers’ and ’definitely believers’, more than half of them perform religious practices: ’irregularly’, ’once in a blue Moon’, or not at all. Many people reveal references to procreation that are inconsistent with the moral principles proclaimed by the Church. This situation requires an answer to the question: ’what ought you do to make things as it should be?’ The opportunity and hope for recovery is the program implemented as part of the premarital course for brides nad grooms, as well as the knowledge, skills and commitment of the priests and family life counselors who lead it. You can see how important and responsible they have a task to fulfill. However, it also seems necessary to extend this responsibility to the whole of society. So that, thanks to the earlier, morally correct and family-oriented education of clients, priests and counselors would not have to make up for the lost time or correct someone’s mistakes.